1978
DOI: 10.1111/j.1348-0421.1978.tb00409.x
|View full text |Cite
|
Sign up to set email alerts
|

Speculation and C2 Toxin Production by Clostridium botulinum Type C Strains Producing No C1 Toxin

Abstract: All of the 8 strains that were previously assumed to be nontoxigenicClostridium botulinum type C were re-examined for their toxigenicity and were demonstrated by trypsinization of the culture filtrates to produce C2 toxin under improved cultural conditions.One per cent glucose added to trypticase peptone medium enhanced C2 toxin production.The larger the spore population, the higher the C2 toxicity and when spore population was smaller than a level of 104/ml, no C2 toxicity was demonstrated.The C2 toxin was pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 6 publications
1
24
0
Order By: Relevance
“…Each "A" and "B" component of the Clostridium and Bacillus binary toxins, but not those from C2, is respectively synthesized with a signal peptide consisting of 29 to 49 and 39 to 47 residues (331). These findings are consistent with proteins secreted during logarithmic growth; however, the C2 toxin is evident from sporulating C. botulinum only after sporangium lysis (289,331). It was recently shown that an extracellular chaperone protein, PrsA, is important for efficient folding and secretion of PA83 from Bacillus species via a Sec-dependent route (477), but it is unknown if similar chaperones play any role with binary toxin components produced by the other bacilli.…”
Section: Biochemistry Genetics and Proteolytic Activationsupporting
confidence: 73%
See 1 more Smart Citation
“…Each "A" and "B" component of the Clostridium and Bacillus binary toxins, but not those from C2, is respectively synthesized with a signal peptide consisting of 29 to 49 and 39 to 47 residues (331). These findings are consistent with proteins secreted during logarithmic growth; however, the C2 toxin is evident from sporulating C. botulinum only after sporangium lysis (289,331). It was recently shown that an extracellular chaperone protein, PrsA, is important for efficient folding and secretion of PA83 from Bacillus species via a Sec-dependent route (477), but it is unknown if similar chaperones play any role with binary toxin components produced by the other bacilli.…”
Section: Biochemistry Genetics and Proteolytic Activationsupporting
confidence: 73%
“…However, the binary C2 enterotoxin produced by toxin types C and D is devoid of neurotoxicity but implicated in a fatal enteric disease of waterfowl, is cytopathic for many different cell types, and induces vascular permeability, necrotic-hemorrhagic lesions, and a lethal fluid accumulation in the lungs and intestinal tracts of various animals (113,189,191,221,276,297,298,300,302,303,(305)(306)(307)(308)390). C2 toxin is synthesized by C. botulinum during sporulation (289) and incorporated into the spore coat (481), which is akin to the single-chain enterotoxin of C. perfringens or protective antigen from B. anthracis edema and lethal toxins (93,130,364,371,465,466). Much of the pioneering work on characterizing the cell binding and translocation component (C2II), as well as the enzyme component (C2I), of C2 toxin was initiated by Ohishi and coworkers throughout the 1980s.…”
Section: Botulinum C2 Toxinmentioning
confidence: 99%
“…Serial 10-fold dilutions were prepared in the dilution solution previously described (16). Samples of 0.1 ml of each serial dilution (10-1 to were plated onto CCFA (5) modified by the addition of 300 I'g of cycloserine (Sigma Chemical Co., St. Louis, Mo., U.S.A.) per ml, 10 I'g of cefoxitin (Merck Sharp & Dohme Research Laboratory, West Point, Pa., U.S.A.) per ml, and l0l'g of lysozyme (Seikagaku Kogyo, Tokyo) per ml, which had been stored in an anaerobic jar under hydrogen gas for 18 to 24 hr before use.…”
Section: Methodsmentioning
confidence: 99%
“…Toxin expression appears to be maximal in stationary phase, and the highest levels of toxin production are generally found in cell populations which undergo rapid autolysis and do not sporulate [428,429]. Only in the case of type C 2 toxin has an association between toxin production and sporulation been reported [430].…”
Section: Solvent Formationmentioning
confidence: 99%